T Lymphocyte-Macrophage Hybrid Membrane-Coated Biomimetic Nanoparticles Alleviate Myocarditis via Suppressing Pyroptosis by Targeting Gene Silencing - Xiong Y; Zhang Z; Liu S; Shen L; Zheng L; Ding L; Liu L; Wu L; Hu Z; Li L; Hu Z; Zhang Z; et al. (International Journal of Nanomedicine)
Yulong Xiong,1,2,* Zhenhao Zhang,1,2,* Shangyu Liu,1,2 Lishui Shen,1,2 Lihui Zheng,1,2 Ligang Ding,1,2 Limin Liu,1 Lingmin Wu,1 Zhicheng Hu,1 Le Li,1 Zhao Hu,1 Zhuxin Zhang,1 Likun Zhou,1 Mengtong Xu,1 Yan Yao1,2 1Department of Cardiology, Fuwai Hospital, National Center for Cardiovascular Diseases, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People’s Republic of China; 2State Key Laboratory of Cardiovascular Disease, Fuwai Hospital, National Center for Cardiovascular Diseases, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yan Yao, Department of Cardiology, Fuwai Hospital, National Center for Cardiovascular Diseases, Chinese Academy of Medical Sciences and Peking Union Medical College, 167A Beilishi Road, Xi Cheng District, Beijing, 100037, People’s Republic of China, Email ianyao@263.net.cnIntroduction: Nanomedicine coated with cell membranes has attracted increasing attention for its enhanced targeting capability and biocompatibility. Based on previous research, we identified interferon regulatory factor 1 (IRF1)-mediated macrophage pyroptosis as a potential therapeutic target for myocarditis. Herein, we fabricated an innovative immune cell membrane-coated zeolitic imidazolate framework-8 (ZIF-8) nano-delivery platform and explored its effects on myocarditis.Methods: ZIF-8 nanoparticles loaded with siRNA targeting IRF1 (siIRF1) were coated with a T lymphocyte-macrophage hybrid membrane (siIRF1@ZIF@HM NPs) via sonication and extrusion. The morphological and biological characteristics of the nanoparticles were evaluated using transmission electron microscopy (TEM) and dynamic light scattering (DLS). Cellular cytotoxicity was assessed by a cell counting kit-8 assay. Cellular uptake and endo-lysosomal escape in M1-differentiated macrophages were visualized via fluorescence microscopy. The targeting specificity and anti-myocarditis effects were evaluated in an experimental autoimmune myocarditis (EAM) mouse model. The anti-pyroptosis effects were assessed by Western blot analysis both in vivo and in vitro.Results: Transcriptional sequencing identified T lymphocytes and macrophages as suitable membrane sources. The ZIF-8 nanoparticles exhibited high siRNA loading capacity and pH responsiveness, enabling an efficient release of siIRF1 from endo-lysosomes to the cytoplasm in macrophages. The hybrid membrane coating enabled specific targeting of M1 macrophages both in vivo and in vitro. Furthermore, delivery of siIRF1 effectively suppressed IRF1 expression and inhibited pyroptosis in IFN-γ-stimulated macrophages. Intravenous injection of siIRF1@ZIF@HM NPs significantly alleviated myocarditis progression without evident side effects.Conclusion: The siIRF1 nanotherapeutic approach shows potential for attenuating myocardial inflammation and mitigating myocarditis progression. Our study highlights the promise of this customized biomimetic nano-delivery system for treating inflammatory diseases. Keywords: hybrid membrane, myocarditis, macrophage, pyroptosis, small interfering RNA, immunotherapy